The Potential Impact of Structured Read-Aloud on Middle School Reading Achievement - Jennifer Kohart Marchessault; Karen H Larwin (Institute of Advanced Engineering and Science, 2014)
Read-aloud is a technique predominantly utilized at the elementary level. This study was designed to research the effectiveness of this technique at the middle school level, specifically, students who were not receiving special education or additional reading intervention services. For the current investigation, students in two middle schools within the same Virginia school district were assigned to receive the treatment of Structured Read-Aloud or received traditional middle-school reading instruction. These students were tested using the Diagnostic Online Reading Assessment (DORA) both in the fall before the intervention was implemented, and then again in the spring of the same year to assess gains. Results indicate that the use of Read-Aloud instruction had an impact on student DORA scores and implications of the research are considered. DOI: http://dx.doi.org/10.11591/ijere.v3i3.6463